2002
DOI: 10.1016/s0164-0704(02)00055-1
|View full text |Cite
|
Sign up to set email alerts
|

The state of macroeconomic forecasting

Abstract: Macroeconomic forecasts are used extensively in industry and government The historical accuracy of US and UK forecasts are examined in the light of different approaches to evaluating macro forecasts. Issues discussed include the comparative accuracy of macroeconometric models compared to their time series alternatives, whether the forecasting record has improved over time, the rationality of macroeconomic forecasts and how a forecasting service should be chosen. The role of judgement in producing the forecasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
92
0
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(109 citation statements)
references
References 122 publications
10
92
0
7
Order By: Relevance
“…However, Fildes and Stekler (2002) note that most US and UK recessions were not predicted in advance, but neither did economists make many predictions of peaks that did not occur. 15 More recently, Sinclair et al (forthcoming) analyzed the directional accuracy of the Fed's forecasts of GDP and inflation and showed that the predictions of increases and decreases in the inflation rate were not associated with the actual changes in that rate.…”
Section: A Directional Errorsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, Fildes and Stekler (2002) note that most US and UK recessions were not predicted in advance, but neither did economists make many predictions of peaks that did not occur. 15 More recently, Sinclair et al (forthcoming) analyzed the directional accuracy of the Fed's forecasts of GDP and inflation and showed that the predictions of increases and decreases in the inflation rate were not associated with the actual changes in that rate.…”
Section: A Directional Errorsmentioning
confidence: 99%
“…I have been involved in two survey papers that have summarized and synthesized the results of these studies. One looks at US and UK forecasts (Fildes and Stekler, 2002). The other does a similar analysis of the G7 (excluding the US) predictions.…”
Section: Findings From Forecast Evaluations (Of Gdp Growth and Inmentioning
confidence: 99%
See 2 more Smart Citations
“…In the economics sphere point forecasts of the conditional mean or some other measure of the central tendency have been the main focus (see, e.g., Mincer and Zarnowitz (1969), Figlewski andWachtel (1981), Zarnowitz (1985), Keane and Runkle (1990), Davies and Lahiri (1995), Stekler (2002) and Fildes and Stekler (2002)),…”
Section: Introductionmentioning
confidence: 99%